Skrytá zlomenina acetabula prokázaná pri vysetrení MR - Drugová, B; Kutácek, M; Syrůcek, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2005)
The authors describe the case of a 35-year-old man with an injury to the left hip joint. When examined at the surgical ward, the patient complained of pain and restricted motion of the left hip. No traumatic changes in the left hip joint were revealed on X-ray and CT examination. When checked-up 13 days later, the patients still complained of persistent pain and restricted movement. Because of the discrepancy between the results of X-ray and clinical examinations, magnetic resonance imaging was recommended. This revealed an infraction of the roof of the acetabulum without trauma to the soft joint tissues and adjacent muscles. A retrospective analysis of the X-ray and CT examination data showed an infraction of the acetabular roof on CT scans. The authors emphasize the role of non-invasive magnetic resonance imaging in the diagnosis of occult fractures.
Keywords: počítačová rentgenová tomografie; fraktury kostí; Magnetic Resonance Imaging; acetabulum; dospělí; Adult; magnetická rezonanční tomografie; Acetabulum; Humans; mužské pohlaví; Male; lidé; Tomography, X-Ray Computed; Fractures, Bone